Behavioral and Neurochemical Effects of Extra Virgin Olive Oil Total Phenolic Content and Sideritis Extract in Female Mice - Nikolaos Kokras (Molecules, 2020)
The aim of this study was to determine the cognitive and behavioral effects of extra virgin olive oil total phenolic content (TPC) and Sideritis (SID) extracts in female mice, and identify the associated neurochemical changes in the hippocampus and the prefrontal cortex. All animals received intraperitoneal low or high doses of TPC, SID or vehicle treatment for 7 days and were subjected to the Open Field (OF), Novel Object Recognition (NOR) and Tail Suspension Test (TST). The prefrontal cortex and hippocampus were dissected for analysis of neurotransmitters and aminoacids with high performance liquid chromatography with electrochemical detection (HPLC-ED). Both TPC doses enhanced vertical activity and center entries in the OF, which could indicate an anxiolytic-like effect. In addition, TPC enhanced non-spatial working memory and, in high doses, exerted antidepressant effects. On the other hand, high SID doses remarkably decreased the animals’ overall activity. Locomotor and exploratory activities were closely associated with cortical increases in serotonin turnover induced by both treatments. Cognitive performance was linked to glutamate level changes. Furthermore, TPC reduced cortical taurine levels, while SID reduced cortical aspartate levels. TPC seems to have promising cognitive, anxiolytic and antidepressant effects, whereas SID has sedative effects in high doses. Both extracts act in the brain, but their specific actions and properties merit further exploration.